Microanatomical observation of Trachea in Sheep - S. Rajathi,; Jayasri, K,; Achuthanandhan, K.S,; S. Muthukrishnan, (Indian Journal of Veterinary Anatomy, 2024)
The aim of the present study was to analyze the microanatomical features of the trachea of sheep. The trachea was collected from the cervical and thoracic regions of six sheep (n=6) from the nearby slaughter and retail outlets. The trachea of sheep is a tubular structure that begins at the cricoid cartilage of the larynx and ends at where it bifurcates to form the principal bronchi, composed of series of incomplete rings that were incomplete dorsally. The small pieces of trachea were collected, fixed and routine histological processing were done. The sections of 5–6 micron thickness were cut and normal and special staining procedures were followed. The histological study showed the trachea was lined by pseudo stratified ciliated columnar epithelium with goblet cells. The wall of trachea consists of mucosa, submucosa, hyaline cartilage and adventitia with huge proportion of tracheal glands. The trachealis muscle was composed of elastic fibers interrupted with smooth fibers.